2020
DOI: 10.5222/mmj.2020.68466
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hearing Loss Among Babies in the Neonatal Intensive Care Unit in a Tertiary Hospital in Malaysia

Abstract: Objective: To study the prevalence of hearing loss (HL) and to identify the possible risk factors causing HL. Methods: This retrospective study was conducted from January 2014-December 2016 at a tertiary hospital in Malaysia. All neonates admitted to the neonatal intensive care unit (NICU), Universiti Kebangsaan Malaysia Medical Centre (UKMMC) were screened with a two-step protocol using an automated auditory brain response (AABR) and/or Otoacoustic Emission and auditory brain response (ABR). Descriptive analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Follow-up telephone interviews were performed between September 1 and November 30, 2021. Hearing status at the time of the telephone interview was recorded, including diagnosis of hearing loss, degree of hearing loss (mild, moderate, severe, or profound), symptoms (difficulty in hearing, communication, or speech), risk factors, 13 , 14 , 15 , 17 , 18 , 19 , 20 and treatment (cochlear implant, hearing aids, or speech therapy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up telephone interviews were performed between September 1 and November 30, 2021. Hearing status at the time of the telephone interview was recorded, including diagnosis of hearing loss, degree of hearing loss (mild, moderate, severe, or profound), symptoms (difficulty in hearing, communication, or speech), risk factors, 13 , 14 , 15 , 17 , 18 , 19 , 20 and treatment (cochlear implant, hearing aids, or speech therapy).…”
Section: Methodsmentioning
confidence: 99%
“… 7 Previous studies have shown that approximately 25% of cases of hearing loss are missed by existing newborn hearing screening (NBHS) programs, wherein two-thirds receive a diagnosis of severe to profound hearing loss later. 11 , 12 Previous studies have indicated that hearing loss among newborns in the NICU was associated not only with clinical risk factors, such as cytomegalovirus infection, craniofacial malformation, family history of hearing loss, duration of NICU stay, oxygen exposure, or low birth weight, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 but also with genetic disorders, which have been shown with the wider use of genetic testing to be associated with hearing loss. 21 Microarray or limited genomic sequencing were used in screening for underlying hearing loss in the general neonatal population because of its low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, considering the contradictory results found in different studies, a largerscale study involving a diverse population of children could provide more comprehensive insights into the relationship between mechanical ventilator use and hearing impairments. 19 There are several limitations in this study. First, history of drug used in infants were not assessed in this study.…”
Section: Discussionmentioning
confidence: 92%
“…A Japanese study in 2019 studied risk factors of hearing loss in 1071 NICU infants, and reported that oxygen administration and chromosomal aberrations were the risk factors [27]. However, a Malaysian study in 2020, which evaluated 2713 infants in NICU, reported that only craniofacial anomalies were the risk factors of hearing loss [28]. A Chinese survey of 616,940 households consisting of disabled people and children aged 0-6 years in 2020, reported that lower annual family income, male children, larger household size, single-mother family, and lower levels of maternal and paternal education were the social risk factors for hearing loss; however, this was just a survey and not a study of NICU infants [29].…”
Section: Discussionmentioning
confidence: 99%